Samin Community: Man, God, Nature in Daily Social Life - Rohmat Djoko Prakosa (Javanologi: International Journal of Javanese Studies, 2024)
This article describes the religiosity and spirituality of Samin people in their daily life. Behind egalitarian attitude is the deep religiosity and spirituality that reflects the cosmic integrity of society guided by the values of wisdom in response to nature’s determination of changing social and cultural dynamics. This article writing is based on field researched strengthened by the reference to previous library references and studies. In everyday life, Samin people express the depth of religion and spirituality. As the part of Java, Samin community performs purification reflected in the terms of wong dam, wong peniten, Samin. The social practice of life harmony, honesty, self surrender to God expressed in terms of sabar trokal reflects profound social piety. Public relations in the natural environment, social culture, religious relations with God reflect an unanimous and complete harmony. Keywords: Samin, social, community.